2020
DOI: 10.1177/0025802420914807
|View full text |Cite
|
Sign up to set email alerts
|

Forensic investigation of arson residue by infrared and Raman spectroscopy: From conventional to non-destructive techniques

Abstract: Arson can result in highly challenging and complicated crime scenes. Much physical evidence undergoes chemical degradation because of the destructive nature of fire, while accelerants either completely burn or evaporate, and may be present in traces within any of the decomposed materials. To identify the original material and the accelerant involved, it is necessary to use advanced analytical techniques. Gas chromatography, with different detectors, is one of the most frequently used instruments in fire debris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Yadav et al also reviewed the use of vibrational spectroscopy for arson residues. 140 They determined that, while IR and Raman spectroscopies are valuable due to the capability of nondestructive analysis, most research is focused on the identification of household products. They suggested that spectroscopy research going forward should turn toward ignitable liquid identification and quantification and examine other important materials routinely found in arson cases (paper, cloth, currency notes, wood, metal, and additional matrices).…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…Yadav et al also reviewed the use of vibrational spectroscopy for arson residues. 140 They determined that, while IR and Raman spectroscopies are valuable due to the capability of nondestructive analysis, most research is focused on the identification of household products. They suggested that spectroscopy research going forward should turn toward ignitable liquid identification and quantification and examine other important materials routinely found in arson cases (paper, cloth, currency notes, wood, metal, and additional matrices).…”
Section: T H Imentioning
confidence: 99%
“…While the bulk of the articles referenced used GC-MS methods, some spectroscopy articles were included. Yadav et al also reviewed the use of vibrational spectroscopy for arson residues . They determined that, while IR and Raman spectroscopies are valuable due to the capability of nondestructive analysis, most research is focused on the identification of household products.…”
Section: Chemistry: Trace Evidencementioning
confidence: 99%
“…Yadav et al discussed the use of infrared and Raman spectroscopy in examining fire debris samples [ 77 ]. The article primarily focused on using these techniques to identify polymers in the debris and not on ignitable liquids.…”
Section: Fire Debris Analysismentioning
confidence: 99%
“…A variety of spectroscopic techniques have been reported for analyzing petroleum products in fire debris samples [8]. This includes vapor phase UV-vis [9], electronic aroma detection, [10], laser induced break down [11], and vibrational spectroscopy such as near-IR, mid-IR, and Raman [8] [12] [13] [14]. Most of these spectroscopic studies involved sample pretreatment and complicated extraction methods.…”
Section: Introductionmentioning
confidence: 99%